Dampak Mata Kuliah Kewirausahaan Kebidanan Terhadap Motivasi Mahasiswa Kebidanan Untuk Berwirausaha - Irma Ibrahim (Peneliti.net, 2022)
The Midwifery Entrepreneurship Course is a compulsory subject that must be taken by students of the D3 Midwifery Study Program. This course is organized by the D3 Midwifery Study Program with the aim of equipping students to have a creative spirit in entrepreneurship. The purpose of this study was to describe and analyze facts with the right interpretation of efforts to improve student soft skills through entrepreneurial materials and practices given in the Midwifery Entrepreneurship course. The research approach used in this study is a qualitative approach. After attending midwifery entrepreneurship lectures held by the D3 Midwifery Study Program, students are more confident and creative in creating entrepreneurial products by utilizing local potential such as spices typical of North Maluku into processed food, drinks or traditional medicines that can be beneficial to the human body, and have the courage to jump in or directly run a business that has been carried out with their classmates.